Continuous therapeutic ultrasound in the healing process in rat skin - Viviani de Marque Carrer; João Antonio Palma Setti; Djanira da Luz Veronez; Auristela Duarte Moser
Abstract Introduction : The therapeutic ultrasound is one of the main resources utilized on physical therapy to stimulate the healing due its thermal and mechanic effects. However, your application still not properly standardized. Objective :To analyze the presence of the collagens types I and III stimulated by the ultrasonic wave in continuous mode at the cutaneous injury local for first intention. Material and methods : It was utilized 90 Wistar rats, young adults, with average weight of 230g, divided in 3 groups of 30 animals: control group, treated with ultrasound off; group 1, treated with ultrasound 0.5 W/cm2 and group 2, treated with ultrasound 2.0 W/cm2. Each group was subdivided in 3 subgroups according with the healing phases, 3, 7 and 21 days of consecutive therapeutic sessions. The ultrasound therapy began 24 hours after the termination of the surgical act, at the dorsal region, applying frequency of 3 MHz and intensities 0.5 W/cm2 and 2.0 W/cm2 during 5 minutes under sliding technique. Later, the animals were sacrificed according to the healing phases for removal of incisional area and histological analyses. Conclusions : The results allowed conclude that the continuous mode of therapeutic ultrasound in the intensities 0.5 W/cm2 and 2.0 W/cm2promoted stimulus to formation of collagens types I and III in the lesion area for first intention.